Still-camera multiview Spectral Optical Flow Imaging for 3D operating-deflection-shape identification. (1st May 2021) - Gorjup, Domen; Slavič, Janko; Babnik, Aleš; Boltežar, Miha
Graphical abstract: Highlights: The Spectral Optical Flow Imaging method is extended for multiview measurements. 3D operating deflection shapes are measured using a single still-frame camera. The effects of multiple-view triangulation on measurement precision are observed. Compared to DIC, image data sizes are reduced by two orders of magnitudes. Compared to DIC, processing times are reduced by four orders of magnitude. Abstract: To measure high-frequency 3D vibrations, multi-camera, high-speed imaging hardware is normally required. An alternative using still-frame cameras was recently introduced with the Spectral Optical Flow Imaging (SOFI) method. In this research, the SOFI method is extended to multiview measurements of spatial operating deflection shapes. This is achieved by utilizing harmonically controlled illumination to perform an analogue Fourier transform on image-intensity data in multiple camera views. The obtained multiview displacement spectra are combined with geometrical data to perform frequency-domain triangulation and reconstruct spatial deflection shapes. By introducing additional camera views into the image-based measurement, its field of view is extended and the signal-to-noise ratio of the final result is increased. For linear, time-invariant mechanical structures under stationary excitation, full-field 3D measurements of high-frequency vibrations can be performed using a single still-frame monochrome camera. The proposed method identifies displacements in the frequency domain directly on the camera sensor, resulting in orders-of-magnitude smaller data sizes and post-processing times compared with conventional multiview image-based methods.